Robots and extensive margins of exports: Evidence for manufacturing firms from 27 EU countries - Joachim Wagner (Kiel Centre for Globalization (KCG), 2024)
The use of robots by firms can be expected to go hand in hand with higher productivity, higher product quality and more product innovation, which should be positively related to export activities. This paper uses firm level data from the Flash Eurobarometer 486 survey conducted in February - May 2020 to investigate the link between the use of robots and export activities in manufacturing enterprises from the 27 member countries of the European Union. Applying standard parametric econometric models and a new machine-learning estimator, Kernel-Regularized Least Squares (KRLS), we find that firms which use robots do more often export, do more often export to various destinations all over the world, and do export to more different destinations. The estimated robots premium for extensive margins of exports is statistically highly significant after controlling for firm size, firm age, patents, and country. Furthermore, the size of this premium can be considered to be large. Extensive margins of exports and the use of robots are positively related.
Keywords: D22; F14; 330; Robots; exports; firm level data; Flash Eurobarometer 486; kernel-regularized leastsquares (KRLS)